Global justice and climate governance : bridging theory and practice - Dietzel, Alix, 1988- (Studies in global justice and human rights., 2019)
This text evaluates the global response to climate change from a cosmopolitan justice perspective. Investigating the role of states, cities, corporations, and non-governmental organisations in the post-Paris Agreement era, Dietzel provides fresh insight into the 'big picture' of climate change (mis)management.